Age Estimation by Clinico-Radiological Examination of Third Molar Teeth: A Study from Delhi - Rani, Anju; Khanna, S K; Mittal, A K; Grewal, Harpreet; Behera , C (Journal of Indian Academy of Forensic Medicine, 2015)
The aim of present study was to estimate the age by studying various stages of eruption and  development of third molar teeth of different quadrant in age group of 15-25 years. A total 100 patients  including equal number of males and females were examined clinically as well as radiologically  (orthopantomograms). Demirjian’s staging (A-H) was used for chronological evaluation of the maxillary  and mandibular third molars. The study showed that the eruption of the third molar tooth was earlier in  males as compared to the females and statistically significant difference in left upper, left lower and right  lower quadrants. Using the regression analysis it was concluded that for all four quadrants chronological  age had a positive linear relationship with dental stage. The right maxillary molar had the strongest  relation than other quadrants. However, values in this study were not found to be statistically significant  which may be due to the less number of subjects examined and the higher age taken for the Demirjian’s  staging.
Keywords: Third molar; Chronological age; Orthopantomograms; Demirjian’s staging